Desain Konten Instagram Sebagai Optimalisasi Media Promosi Allisa Cake - Hardina Risma Zakiya; Fitro Nur Hakim; Setiyo Prihatmoko (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The Allisa Cake business was founded by Mrs. Nora in 2016, a housewife located in Krapyak, West Semarang, Semarang City, Central Java. The products produced are cakes or bread which are marketed offline and online. However, online marketing has not met the expected targets, so appropriate promotional media is needed, in order to introduce the product to the public and to optimize promotional media. This research designs Instagram content that makes it easier to understand products and designs Instagram content that follows trends.The method used in this research is ADDIE developed by Dick and Carry, the development design with the ADDIE design aims to develop and validate the product. Meanwhile, the software used includes Corel Draw and Adobe Photoshop.Data collection was carried out by interviewing business owners, making observations and studying literature. After getting the data, create a product design and then apply it to the Instagram Feed design concept. The design stages are in the form of Thumbnail visualization, Tightissue and Final Design. The research produces Instagram content that contains information to make it easier to understand the product and the content design follows trends as the main promotional media.